CH Atelier : where magic is weaved into every stitch - Chee, Cynthia Qian Ee (2024)
CH Atelier's business plan presents a bold and necessary response to the pressing environmental and ethical issues plaguing the fast fashion industry. Our approach is twofold: firstly, to provide production and sampling services to B2B clients with our skilled workmanship, including both local and international designers, and secondly, to create custom, sustainable, and eco-friendly gowns for individual consumers.